Electrofugality of some ferrocenylphenylmethyl cations - Jurić, Sandra (Array, 2019)
The electrofugality scale has been extended with new substituted ferrocenylphenylmethyl cations 1-4. Ef values were determined by applying the linear free energy relationship (LFER): log k = sf (Ef + Nf). Due to ability of the ferrocene moiety to efficiently stabilize the positive charge, ferrocenylphenylmethyl cations constitute a group of very powerful electrofuges (Ef >1). Impact of the phenyl group in ferrocenylphenylmethyl derivatives on stabilization of the positive charge is considerably leveled by the ferrocenyl group, so the rate effect of the alkyl substituents (methyl, ethyl and tert-butyl) on the phenyl ring is suppressed, causing narrow range of Ef parameters. Lack of breakdown of Hammett-Brown plot if the rates for the complete set of substrates 1–5 have been correlated, indicates that the ferrocenyl group in α-position diminishes the stabilizing effects of electron-donating substituents as well.